Using a mixed method to develop consensus-based aims, contents, intended learning outcomes, teaching, and evaluation methods for a course on epilepsy for postgraduate or continuing education in community health nursing programs - Ramzi Shawahna (BMC, 2021)
Abstract Background Knowledge deficits with regard to epilepsy have been reported among healthcare professionals. This study was conducted to develop consensus-based aims, contents, intended learning outcomes, teaching, and evaluation methods for a course on epilepsy for postgraduate or continuing education in community health nursing programs. Methods A mixed method which combined a thorough search of literature, the nominal group technique, the Delphi technique, and survey of students’ agreement was used. The databases MEDLINE/PUBMED, EMBASE, COCHRANE, CInAHL/EBESCO, SCOPUS, Google Scholar, Google Books, and Amazon were searched to identify potential aims, topics/contents, intended learning outcomes, teaching, and evaluation methods. Discussions and deliberations in serial meetings based on the nominal group technique were attended by educators/academicians (n = 12), neurologists (n = 2), practicing nurses (n = 5), pharmacists (n = 2), patients with epilepsy (n = 2), and students in postgraduate and continuing education programs (n = 7) to supplement and refine the data collected from the literature. The qualitative data were analyzed using RQDA tool for R. The Delphi technique was used among educators/academicians (n = 15), neurologists (n = 2), practicing nurses (n = 5), pharmacists (n = 2), patients with epilepsy (n = 3), and students in postgraduate and continuing education programs (n = 8) to achieve formal consensus. Results Consensus was achieved on 6 aims, 16 intended learning outcomes, and 27 topics in the course. Of the topics, 13 were relevant to nature of epilepsy and seizures, 2 were relevant to the impact of epilepsy and seizures on different life aspects of patients with epilepsy, 4 were relevant to advocating for the patients and supporting their choices, 5 were relevant to educating patients and their caregivers, and 3 were relevant to assessments and services. Conclusion Consensus-based aims, topics/contents, intended learning outcomes, teaching, and evaluation methods of a course on epilepsy for postgraduate or continuing education in community health nursing programs were developed. Consensus-based courses could bridge knowledge gaps and improve educating community health nursing programs on epilepsy. Further studies are needed to determine if such consensus-based courses could promote care of patients with epilepsy.